Penentuan Kadar Minyak Atsiri Daun Kayu Manis (Cinnamomum burmannii, Blume) dengan Perlakuan Pendahuluan pada Daun - Reno Irwanto; Anwar Kasim; Sahadi Didi Ismanto (Jurnal Teknologi Pengolahan Pertanian, 2022)
Essential oils are essential oils that have a characteristic smell of plants and are volatile. Essential oils can be obtained by several processes such as distillation, enfleuration, maceration and extraction. Distillation is a technique used to separate the desired compound (essential oil) based on differences in boiling points. The detailing process is carried out in several ways including pre-treatment in the form of withering, drying and size reduction. Distillation can also be done by giving different distillation times. The distillation process was carried out through the stages of preparation of cinnamon leaves for determination of essential oil content, preparation of cinnamon leaves for pilot-scale distillation, separation of cinnamon leaf essential oil with distilled water, as well as analysis of the physical and chemical properties of distilled cinnamon leaf essential oil. This study used a Factorial Completely Randomized Design (CRD) with differences in distillation time (3 hours, 4 hours, 5 hours, 6 hours, and 7 hours), and leaf conditions (fresh and dry leaf conditions) for 2 replications. Data analysis was carried out with the F test at a 5% significance level, if the results were significantly different then the analysis continued with the "Duncan's New Multiple Range Test" (DNMRT) test. The results showed that the optimum distillation time was 5 hours for fresh and dry leaves with chemical and physical properties, namely yield of 0.39%, specific gravity of 1.0015, refractive index of 1.526, optical rotation -4.640 and cinnamaldehyde content of 14.21%.